Evidence of denser MgSiO(3) glass above 133 gigapascal (GPa) and implications for remnants of ultradense silicate melt from a deep magma ocean - Murakami, Motohiko (National Academy of Sciences, 2011)
Ultralow velocity zones are the largest seismic anomalies in the mantle, with 10–30% seismic velocity reduction observed in thin layers less than 20–40 km thick, just above the Earth’s core-mantle boundary (CMB). The presence of silicate melts, possibly a remnant of a deep magma ocean in the early Earth, have been proposed to explain ultralow velocity zones. It is, however, still an open question as to whether such silicate melts are gravitationally stable at the pressure conditions above the CMB. Fe enrichment is usually invoked to explain why melts would remain at the CMB, but this has not been substantiated experimentally. Here we report in situ high-pressure acoustic velocity measurements that suggest a new transformation to a denser structure of MgSiO(3) glass at pressures close to those of the CMB. The result suggests that MgSiO(3) melt is likely to become denser than crystalline MgSiO(3) above the CMB. The presence of negatively buoyant and gravitationally stable silicate melts at the bottom of the mantle, would provide a mechanism for observed ultralow seismic velocities above the CMB without enrichment of Fe in the melt. An ultradense melt phase and its geochemical inventory would be isolated from overlying convective flow over geologic time.